Characteristics Associated With Recruitment and Re-contact in Mayo Clinic Biobank - Hathcock, Matthew A.; Kirt, Christine; Ryu, Euijung; Bublitz, Josh; Gupta, Ruchi; Wang, Liwei; Thibodeau, Stephen N.; Larson, Nicole L.; Cicek, Mine S.; Cerhan, James R.; Olson, Janet E. (Frontiers in Public Health, 2020)
Objective: To better understand the characteristics associated with a participant’s willingness to consent to the Mayo Clinic Biobank (MCB) and examine factors associated with willingness to participate in follow-up studies embedded within MCB that require re-contact and participant approval. Participants and Methods: Consent rates were compared across patient demographics to the MCB. Rates of participation to follow-up studies were also compared across demographics and request types. Results: Among 272,102 Mayo Clinic patients invited to the MCB, 48,314 (19%) consented across the three recruitment sites within 90 days of initial invitation. A significant age by gender interaction was identified, showing young males consent at a lower rate than young females and older males consent at a higher rate than older females. Over the recruitment time frame of 2009-2015, there was a significant decrease in consent rates (decline of 2.5%/year). Of the 57,041 consented MCB participants, 33,487 participants (59%) have been invited to participate in follow-up studies via re-contact. Follow-up studies of the MCB may require participants to provide additional samples, complete questionnaires, and/or release their identity to a research team. MCB participants have been invited to enroll in a median of 2 studies (IQR: 1 to 3). 71% of participants consented to at least one follow-up study, with individual follow-up study consent rates ranging from 14 to 87% depending on study type, with a median consent rate of 61%. Studies requesting return of a questionnaire had the highest participation rates. White participants, older participants, and participants with some college or a degree were significantly more likely to participate to follow-up studies, while there was no association with gender. Conclusion: Recruitment of participants to a general biobank follows the same trends commonly seen in other recruitments biobanks. While participation rates to follow-up studies are higher than observed in new recruitment studies we find many of the same trends: white, older, and more educated participants have higher participation rates. Requirements of the follow-up studies also appear to play a role in a participant’s willingness for further participation.